TGFβ regulates persistent neuroinflammation by controlling Th1 polarization and ROS production via monocyte‐derived dendritic cells. Issue 11 (1st August 2016) - Parsa, Roham; Lund, Harald; Tosevski, Ivana; Zhang, Xing‐Mei; Malipiero, Ursula; Beckervordersandforth, Jan; Merkler, Doron; Prinz, Marco; Gyllenberg, Alexandra; James, Tojo; Warnecke, Andreas; Hillert, Jan; et al.
Abstract : Intracerebral levels of Transforming Growth Factor beta (TGFβ) rise rapidly during the onset of experimental autoimmune encephalomyelitis (EAE), a mouse model of Multiple Sclerosis (MS). We addressed the role of TGFβ responsiveness in EAE by targeting the TGFβ receptor in myeloid cells, determining that Tgfbr2 was specifically targeted in monocyte‐derived dendritic cells (moDCs) but not in CNS resident microglia by using bone‐marrow chimeric mice. TGFβ responsiveness in moDCs was necessary for the remission phase since LysM Cre Tgfbr2 fl/fl mice developed a chronic form of EAE characterized by severe demyelination and extensive infiltration of activated moDCs in the CNS. Tgfbr2 deficiency resulted in increased moDC IL‐12 secretion that skewed T cells to produce IFN‐γ, which in turn enhanced the production of moDC‐derived reactive oxygen species that promote oxidative damage and demyelination. We identified SNPs in the human NOX2 (CYBB) gene that associated with the severity of MS, and significantly increased CYBB expression was recorded in PBMCs from both MS patients and from MS severity risk allele rs72619425‐A carrying individuals. We thus identify a novel myeloid cell‐T cell activation loop active in the CNS during chronic disease that could be therapeutically targeted. GLIA 2016;64:1925–1937 Main Points: TGFβ controls a moDC‐Th1 activation loop in the CNS that causes chronic MOG‐EAE without remission and is characterized by severe demyelination and oxidative damage. TGFβ limits ROS production by Nox2, a gene associated with MS severity in humans.